PLC-based mobile mecanum robot as multipurpose vehicle - Wongvanich, Napasool; Gulpanich, Suphan; Suesat, Taweepol; Kongratana, Viriya (My University, 2018)
This paper presents the mobile robot that is able to mobilize in every direction through the use of four DC-motors-powered mecanum wheels. Each wheel can be programmed to rotate independently, allowing the vehicle to move in any direction without first turning, and thus can be used to navigate in narrow fields. The robot is controlled through the use of the Programmable Logic Controller CP1H-XA40DT-D, that takes the user intended direction from a joystick command and converts this command into movement vectors in conjunction to the mathematical kinematics model of the mecanum wheels. The motors themselves are controlled from the PWM signals. Two speed experiments were conducted. The first experiment tests the speed of the robot in a no-load environment, whilst the second tests the robot speed in a 50-kg loaded environment. Results show that the maximum attainable speed is around 31.9 ms − 1 with a drop of about 10% for the case of the added load from the no-load condition. This result validates the proposed applicability of the prototype as a wheelchair as well as a self-control shopping cart.
Keywords: Four wheel drive; Mecanum wheel; PLC; PWM Driver